2020
DOI: 10.1186/s40902-020-00287-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-inferiority study of the efficacy of two hyaluronic acid products in post-extraction sockets of impacted third molars

Abstract: Background Hyaluronic acid (HA) is well known to exert an anti-inflammatory effect during oral wound healing and is commonly applied after tooth extraction. However, no double-blind randomized controlled study comparing two hyaluronate mouthwash products has been conducted so far. The aim of this study was to comparatively analyze the efficacy of Mucobarrier® and Aloclair® in terms of clinical symptoms. Results A total of 112 patients were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In all preclinical trials, HyA was applied into the tooth socket after extraction of regularly erupted teeth [ 30 34 ]. The clinical trials were divided into 3 groups according to treatment indication: (1) surgical removal of LM3 (RCT ( n = 10), CT ( n = 1)) [ 35 45 ], (2) extraction of regularly erupted teeth (RCT ( n = 7), non-randomized split-mouth study ( n = 1), prospective case series ( n = 1)) [ 46 – 54 ], and (3) treatment of AO (RCT ( n = 1), prospective case series ( n = 1)) [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all preclinical trials, HyA was applied into the tooth socket after extraction of regularly erupted teeth [ 30 34 ]. The clinical trials were divided into 3 groups according to treatment indication: (1) surgical removal of LM3 (RCT ( n = 10), CT ( n = 1)) [ 35 45 ], (2) extraction of regularly erupted teeth (RCT ( n = 7), non-randomized split-mouth study ( n = 1), prospective case series ( n = 1)) [ 46 – 54 ], and (3) treatment of AO (RCT ( n = 1), prospective case series ( n = 1)) [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In one clinical study, a multicenter study design was reported including 8 medical centers [ 56 ], whereas all other clinical studies were performed in a single department in a university setting. Eleven clinical studies did not report on funding sources, while in 9 clinical studies [ 35 , 36 , 42 , 44 , 45 , 52 , 53 , 56 , 60 ] the funding was provided by the department; however, in 3 out of these 9 studies, the HyA gel was provided by the manufacturer [ 46 , 52 , 53 ]. In a single study, the funding was provided by 3 different research foundations [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, sodium hyaluronate can also strengthen the bond between fibrin and collagen so that blood clots become more stable and less easily damaged. 18 The wound healing process of the extraction socket can also be assessed clinically by the size of the socket wound. The faster the size of the wound decreases, the faster the wound healing process takes place.…”
Section: Discussionmentioning
confidence: 99%
“…A mouthwash with hyaluronic acid and cetylpyridinium chloride was shown to be as effective as a chlorhexidine mouthwash in reducing plaque accumulation [ 83 ]. Furthermore, hyaluronic-acid-containing formulations reduced complications after tooth extractions [ 84 , 85 ]. However, Zorrilla et al showed that the use of a chlorhexidine-chitosan gel resulted in better healing than with the use of a hyaluronic acid gel after oral surgery [ 86 ].…”
Section: Overview On Adjunct Ingredients Used In Hydroxyapatite-based...mentioning
confidence: 99%